Hudson hawk - Silver, Joel; Lehman, Michael irector (Columbia/Tristar Home Video, 1998)
Eddie "The Hawk" Hawkins, the world's most famous cat burglar, who, after 10 years in prison, is ready to go straight. But it's not going to be easy for the Hawk. The mob and the CIA have conspired to blackmail Eddie and his partner (Aiello) into stealing three da Vinci masterpieces from the most heavily-guarded museums in the world.